2009
DOI: 10.1080/09540120902923022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of structural intervention on increasing condom availability and reducing risky sexual behaviours in gay bathhouse attendees

Abstract: The study purpose was to evaluate the effectiveness of a structural intervention in reducing unprotected sexual behaviours, increasing condom accessibility and their relationship to the prevalence of HIV infection and sexually transmitted infections (STIs) in gay bathhouse attendees. A quasi-experimental study with a non-equivalent control group for comparison was conducted at nine gay bathhouses in Taiwan from 2004 to 2006. A structural intervention designed to increase condom distribution and accessibility i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…Of equal importance is the protective effect of condom availability, which corroborates literature discriminating consistent versus inconsistent condom users among MSM [6, 27]. The results of the current study have practical implications, in that it seems useful to place and to distribute condoms at the venue where anal sex commonly takes place.…”
Section: Discussionsupporting
confidence: 83%
“…Of equal importance is the protective effect of condom availability, which corroborates literature discriminating consistent versus inconsistent condom users among MSM [6, 27]. The results of the current study have practical implications, in that it seems useful to place and to distribute condoms at the venue where anal sex commonly takes place.…”
Section: Discussionsupporting
confidence: 83%
“…Additionally, recent research has demonstrated the effectiveness of pilot programs that have sought to partner commercial sex environments with groups offering HIV testing and education onsite. 60,61 Results from these studies have shown that interventions have been efficacious in reducing the spread of HIV and other STIs in such environments and these services are currently being replicated. 61 Consequently, only a small percentage of our overall sample indicated sex party attendance and data on specific acts of sexual behavior during sex parties was not collected during this study.…”
Section: Discussionmentioning
confidence: 98%
“…Other studies have found that having access to condoms was associated with safer sex practices among women who worked in bars in Tijuana, Mexico [37] and decreased unprotected sex among bathhouse patrons in Taiwan [38]. Studies underscore the importance of a supportive social environment for FSWs in China and India, such as a venue's condom availability, managerial support of condom availability, and clinic visitations [39], [40].…”
Section: Discussionmentioning
confidence: 99%